Effect of Fly Ash Use on Compressive Strength and Water Absorption of Paving Block - Nathalie Dwiana; Anang Kristianto (Publikasi Indonesia, 2024)
Paving block is a product of a mixture of mortar which is generally used as a building material and ground surface pavement that can function as a sidewalk or public road that is often passed by pedestrians and vehicles. Mortar mixtures have a composition of cement, fine aggregate, water, and can use other additives. In this study, the additional material used is fly ash. With the right composition and procedures, the addition of fly ash as a cement substitution in the mixture can have a good effect on the compressive strength and water absorption of the paving block. The research was conducted using a mixture of fly ash as much as 10%, 20%, 25%, 30%, 35%, and 40% in laboratory research and 10% and 20% fly ash in research conducted in the field. The mixture used in the manufacture of paving blocks has a cement:sand composition ratio of 1:5. In the implementation of the results of testing the quality requirements of concrete bricks, the highest quality value was found in the range of fly ash use of 10-20%, both research conducted in the laboratory and field research. The highest compressive strength test results in the laboratory had a value of 20.1 MPa in the 10% and 20% variable tests, while for field tests, the highest value was obtained in the variable of using fly ash of 10% with a compressive strength value of 15.74 MPa.